PENINGKATAN KEMAMPUAN REPRESENTASI MATEMATIKA SISWA SMA TUNAS PELITA BINJAI MELALUI PEMBELAJARAN KOOPERATIF BERBASIS MULTIPLE INTELLIGENCE - Suwanto Suwanto; Fitry Wahyuni (MES: Journal of Mathematics Education and Science, 2018)
Abstract. This research aims to determine the increase mathematical representation ability of students with cooperative learning base multiple intelligence. The lower mathematical representation ability and the difficulty in understanding trigonometry and also not facing multiple intelligences is the reason for this research. This research is a quasi experiment that compares two classes with different treatments, cooperative learning based on multiple intelligence and exspositori learning. Learning media in reasech is the RPP and LAS that is validated the expert team. The research instrument was also validated by an expert team and continued with validation, reliability, difficulty and differentiation tests. The analysis used is one-way ANOVA obtained by Fcount (4,342) Ftable (0,05) (4,026) Explained, H0 is accepted, and it can be concluded that the increased ability of mathematical representation in multiple intelligence-based cooperative learning rather than increasing mathematical representation ability in ordinary learning.Keywords: mathematical representation, cooperative learning, multiple intelligence